A fly ash-based magnetic composite material and its preparation method and application
By using fly ash-based magnetic composite materials, the problems of insufficient adsorption capacity and difficulty in recycling of existing adsorbents in heavy metal wastewater treatment are solved, and the effect of efficient removal of divalent mercury in water is achieved, and the cost and environmental impact are reduced.
Patent Information
- Application Number
- CN202410318699.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-03-20
AI Technical Summary
In the existing heavy metal wastewater treatment methods, the adsorbent has problems such as insufficient adsorption capacity, difficulty in recycling, and high cost, making it difficult to effectively remove divalent mercury (Hg(II)) in water.
Fly ash-based magnetic composite material is used, which consists of floating beads, iron salts, ferrous salts and MXene dispersions. Through pickling and the preparation of magnetic powder, a composite material with high adsorption properties and magnetism is formed.
It achieves efficient adsorption and removal of divalent mercury from water, easy to recycle, low cost, simple and non-toxic, and environmentally friendly.
Smart Images

Figure CN118059807B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial wastewater purification and treatment, and specifically relates to a fly ash-based magnetic composite material and a preparation method and application thereof. Background Art
[0002] Heavy metal pollution poses a serious threat to global ecosystems and human health. Mercury is one of the most toxic and widely distributed heavy metals. Mercury and its compounds have been widely used in industries such as precious metal extraction, electronic equipment, and industrial catalysis. Mercury exists in three forms: organic mercury, inorganic mercury, and metallic mercury. Any form of mercury is harmful to the human body and cannot be degraded. Among them, divalent mercury (Hg(Ⅱ)) is the most common form of mercury in water.
[0003] At present, the commonly used methods for heavy metal wastewater treatment include precipitation, adsorption, membrane separation, electrochemical method, etc. Each method has different characteristics and advantages. Among them, the adsorption method has attracted widespread attention due to its unique and convenient operation advantage. In the treatment, adsorption materials with high specific surface area structure or special functional groups can be used to reduce pollutants, thereby reducing the concentration of heavy metal ions in the wastewater. The adsorption method has been used to treat heavy metal wastewater for a long time. The advantages of this method are simple operation, low energy consumption, low investment cost, high efficiency, and no secondary pollution. Therefore, it has good application prospects in the treatment of heavy metal wastewater.
[0004] Commonly used adsorbents mainly include: 1) Carbon-based adsorbents: Carbon-based adsorption refers to the use of solid carbon materials such as activated carbon, carbon nanotubes, graphene and biochar as adsorbents to adsorb heavy metal wastewater, which is a physical adsorption method. However, carbon-based adsorbent materials for the adsorption of heavy metals generally have problems such as insufficient adsorption capacity, low adsorption efficiency, and relatively high cost. 2) Nano adsorbents: such as titanium dioxide, carbon nanotubes and iron oxides. Compared with bulk materials, nanomaterials have better performance in adsorbing toxic ions in water, and as the particle size decreases, the adsorption capacity will increase significantly. However, the most common problem with nanomaterials is that it is difficult to separate them from aqueous solutions, and the secondary pollution caused by this is also relatively serious. 3) Polymer adsorbents: mainly include three categories, namely natural polymer adsorbents, synthetic polymer adsorbents, and polymer composite adsorbents. Among them, natural polymers and their derivative adsorbents have many advantages. They are not only rich in sources, simple in preparation process, and low in cost, but also non-toxic and harmless, and can be naturally biodegraded. Therefore, they have important applications in heavy metal treatment. However, polymer adsorption materials also have many shortcomings, such as low mechanical strength, difficulty in remelting, and instability under strong acid and alkali conditions. 4) Natural mineral adsorbents: mainly clay, perlite, vermiculite, expanded shale, natural zeolite, diatomaceous earth, bentonite and natural sediments. Mineral adsorbents are widely available and easy to obtain, but due to their own structural limitations and defects, they are prone to produce a large amount of heavy metal-containing waste and cause secondary pollution. They may have problems such as low efficiency and difficulty in regeneration in heavy metal adsorption.
[0005] Therefore, it is necessary to develop a heavy metal adsorbent with high adsorption capacity, easy recovery and low cost. Summary of the invention
[0006] The purpose of the present invention is to provide a fly ash-based magnetic composite material and its preparation method and application. The fly ash-based magnetic composite material provided not only ensures a high adsorption and removal effect on Hg (II), but also facilitates recycling due to the introduction of magnetism, and the raw materials used are floating beads separated from fly ash, which turns waste into treasure and reduces costs. In addition, the preparation method provided by the present invention involves a simple process, is non-toxic, and is environmentally friendly, and is suitable for promotion and application.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing a fly ash-based magnetic composite material, comprising the following steps:
[0009] Add the pickled beads to the Fe-containing 3+ and Fe 2+The solution is added, the pH is adjusted to 10, the reaction is stirred at 80° C., and the magnetic beads are obtained by filtering; the magnetic beads are dispersed in a MXene dispersion, the pH is adjusted to 5, ultrasonicated, stirred in an inert atmosphere, filtered, and dried to obtain a fly ash-based magnetic composite material.
[0010] Preferably, the preparation step of the acid-washed floating beads comprises: dispersing the floating beads in a 0.1 mol / L HCl solution, stirring for 1 hour, filtering and drying to obtain the acid-washed floating beads.
[0011] Preferably, the Fe 3+ with Fe 2+ The molar ratio is 2:1.
[0012] Preferably, the Fe-containing 3+ and Fe 2+ The solvent of the solution is ethanol and water in a volume ratio of 1:1.
[0013] Preferably, the stirring reaction time at 80° C. is 3 h.
[0014] Preferably, the pickled beads and the Fe 3+ The mass molar ratio of the magnetic beads to the MXene is 9:1.
[0015] More preferably, the pickled beads and the Fe 3+ The mass molar ratio is 1g:0.87mmol.
[0016] Preferably, the content of MXene in the MXene dispersion is 1 to 4 mg / mL.
[0017] Preferably, the ultrasonication time is 1 hour; and the stirring time under the inert atmosphere is 1 hour.
[0018] The second technical solution of the present invention is to provide a fly ash-based magnetic composite material prepared according to the preparation method of the fly ash-based magnetic composite material.
[0019] The third technical solution of the present invention is to provide an application of the above-mentioned fly ash-based magnetic composite material in the adsorption of divalent mercury.
[0020] The beneficial technical effects of the present invention are as follows:
[0021] (1) The fly ash-based magnetic composite material of the present invention uses floating beads, iron salt, ferrous salt and MXene dispersion as raw materials. The floating beads are carriers, Fe3O4 generated by iron salt and ferrous salt provides magnetism, and MXene in the MXene dispersion enhances its adsorption capacity. The floating beads are loaded with Fe3O4 and MXene, which not only increases magnetism, facilitates subsequent recovery, but also greatly enhances adsorption performance.
[0022] (2) The floating beads used in the present invention are thin-walled hollow beads separated from fly ash. The main components are SiO2 and Al2O3. They have porous structures and large specific surface areas, and are very suitable as carriers for composite adsorbents. By recycling solid waste and turning waste into treasure, not only is land occupation reduced, but also the pollution to the ecological environment is alleviated, and considerable economic benefits can be created.
[0023] (3) Compared with traditional adsorbent materials, the MXene in the MXene dispersion prepared by the present invention has a larger specific surface area, abundant -OH and -O functional groups, and adjustable surface chemical properties, which not only provides a location for surface complexation and ion exchange with Hg(II), but also acts as a reductant for Hg(II). This combined adsorption in situ reduction ability is superior to many other nanomaterial adsorbents and has quite excellent Hg(II) removal performance, which is of great significance for reducing secondary pollution of water bodies.
[0024] (4) The preparation method of the magnetic composite material of the present invention involves a simple process, is non-toxic, and is environmentally friendly, and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention provides a flow chart for preparing a fly ash-based magnetic composite material according to an embodiment of the present invention.
[0026] Figure 2 The XRD patterns of the samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG.
[0027] Figure 3 The magnetization curves of the samples prepared in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0028] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0029] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] The steps of vacuum filtration, ultrasound, centrifugation and the like in the preparation process of the embodiments of the present invention are conventional technical means in the art and are not intended to limit the technical solutions of the present invention.
[0033] The room temperature in the embodiment of the present invention refers to 25±2°C.
[0034] The flow chart of preparing fly ash-based magnetic composite material according to the embodiment of the present invention is shown in Figure 1 .
[0035] Example 1
[0036] 1) Preparation of MXene dispersion: 1 g of lithium fluoride was added to 20 mL of 9 mol / L hydrochloric acid solution. After fully dissolved, 1 g of MAX (Ti3AlC2) was slowly added to the above solution, and stirred and etched (35 ° C, 24 h, speed of 450 r / min). Then, ultrasonic centrifugation was performed to make the pH of the supernatant higher than 6. 40 mL of ethanol was added to the precipitate, ultrasonically treated for 1 h (750 W), centrifuged for 10 min (10000 r / min), and the lower precipitate was collected to obtain MXene few-layer nanosheets. After adding 10 mL of deionized water and ultrasonically treated for 20 min, centrifuged for 3 min (5000 r / min), the black-brown upper liquid was collected to obtain a MXene dispersion with a concentration of 3 mg / mL;
[0037] 2) Pretreatment of floating beads: disperse the floating beads in 0.1 mol / L HCl solution, stir for 1 hour, filter and wash, and vacuum dry at 80°C to obtain acid-washed floating beads;
[0038] 3) Preparation of magnetic powder (Fe3O4 / FA): Weigh 0.2345g (0.87mmol) of FeCl3·6H2O and 0.087g (0.44mmol) of FeCl2·4H2O, add to 100mL of a mixture of ethanol and deionized water (ethanol: water = 1:1), and stir until completely dissolved. Add 1.0g of acid-washed floating beads and stir for 1h. Then add 25wt.% ammonia water dropwise to pH = 10, and stir at 80℃ for 3h. Filter and wash, wash twice with ethanol and deionized water respectively, and dry in a vacuum at 80℃ to obtain magnetic powder;
[0039] 4) Weigh 0.27 g of the magnetic powder prepared in step 3) and disperse it in 10 mL of the MXene dispersion prepared in step 1), add deionized water to obtain 100 mL of the mixed dispersion, add dilute hydrochloric acid to adjust the pH to 5, ultrasonicate for 1 h, stir electrically for 1 h (N2 atmosphere), filter and wash at a pressure of 0.5 MPa, and vacuum dry at 80°C to obtain a fly ash-based magnetic composite powder (MXene / Fe3O4 / FA).
[0040] Example 2
[0041] 1) Preparation of MXene dispersion: 1 g of lithium fluoride was added to 20 mL of 9 mol / L hydrochloric acid solution. After fully dissolved, 1 g of MAX (Ti3AlC2) was slowly added to the above solution, and stirred and etched (35 ° C, 24 h, speed of 450 r / min). Then, ultrasonic centrifugation was performed to make the pH of the supernatant higher than 6. 40 mL of ethanol was added to the precipitate, ultrasonically treated for 1 h (750 W), centrifuged for 10 min (10000 r / min), and the lower precipitate was collected to obtain MXene few-layer nanosheets. After adding 10 mL of deionized water and ultrasonically treated for 20 min, centrifuged for 3 min (5000 r / min), the black-brown upper liquid was collected to obtain a MXene dispersion with a concentration of 3 mg / mL;
[0042] 2) Pretreatment of floating beads: disperse the floating beads in 0.1 mol / L HCl solution, stir for 1 hour, filter and wash, and vacuum dry at 80°C to obtain acid-washed floating beads;
[0043] 3) Preparation of magnetic powder: Weigh 0.7035g (2.6mmol) of FeCl3·6H2O and 0.261g (1.3mmol) of FeCl2·4H2O, add to 100mL of ethanol and deionized water mixture (ethanol: water = 1:1), and stir until completely dissolved. Add 1.0g of acid-washed floating beads and stir for 1h. Then add 25wt.% ammonia water dropwise to pH = 10, and stir at 80℃ for 3h. Filter and wash, wash twice with ethanol and deionized water respectively, and dry in a vacuum at 80℃ to obtain magnetic powder;
[0044] 4) Weigh 0.27 g of the magnetic powder prepared in step 3) and disperse it in 10 mL of the MXene dispersion prepared in step 1), add deionized water to obtain 100 mL of the mixed dispersion, add dilute hydrochloric acid to adjust the pH to 5, ultrasonicate for 1 h, stir electrically for 1 h (N2 atmosphere), filter and wash at a pressure of 0.5 MPa, and vacuum dry at 80°C to obtain a magnetic composite powder.
[0045] Comparative Example 1
[0046] Take 10 g of floating beads and disperse them in 0.1 mol / L HCl solution, stir for 1 h, filter and wash, and vacuum dry at 80°C to obtain acid-washed floating beads.
[0047] Comparative Example 2
[0048] Weigh 0.2345 g (0.87 mmol) of FeCl3·6H2O and 0.087 g (0.44 mmol) of FeCl2·4H2O and add them to 100 mL of a mixture of ethanol and deionized water (ethanol: water = 1:1), and stir until completely dissolved. Add 1.0 g of acid-washed floating beads and stir for 1 h. Then add 25 wt.% ammonia water dropwise to pH = 10, and stir at 80 ° C for 3 h. Filter and wash, wash twice with ethanol and deionized water respectively, and vacuum dry at 80 ° C to obtain magnetic powder.
[0049] Comparative Example 3
[0050] Weigh 0.7035 g (2.6 mmol) of FeCl3·6H2O and 0.261 g (1.3 mmol) of FeCl2·4H2O and add them to 100 mL of a mixture of ethanol and deionized water (ethanol: water = 1:1), and stir until completely dissolved. Add 1.0 g of acid-washed floating beads and stir for 1 h. Then add 25 wt.% ammonia water dropwise to pH = 10, and stir at 80 ° C for 3 h. Filter and wash, wash twice with ethanol and deionized water respectively, and vacuum dry at 80 ° C to obtain magnetic powder.
[0051] A total of 5 samples in the above embodiments and comparative examples were tested for mercury removal performance. The method is to dilute the mercury standard solution with water to obtain a mercury-containing solution of corresponding concentration, then add a certain mass of powder sample to the solution, use an X-ray fluorescence heavy metal analyzer to test the divalent mercury concentration in the solution before and after adding the sample, and calculate the mercury removal efficiency by concentration difference / initial mercury concentration. The operating conditions are: test mode is water, test time is 100 s, initial divalent mercury concentration is 50 mg / L, solution volume is 100 mL, adsorbent dosage is 50 mg, adsorption time is 2 h, and temperature is room temperature. The experimental results are shown in Table 1.
[0052] Table 1 Mercury removal efficiency of five samples in the examples and comparative examples
[0053]
[0054] As can be seen from Table 1, in Comparative Examples 1-2, 3+When the molar mass ratio of the acid-washed floating beads is 0.87 mmol:1 g and the mass ratio of MXene to Fe3O4 / FA is 1:9, the mercury removal efficiency of the fly ash-based magnetic composite material reaches the best, and the adsorption equilibrium is reached in 1 hour, and the adsorption rate is fast; by comparing Examples 1 and 2 with Comparative Examples 1, 2, and 3, it can be seen that compared with the acid-washed floating beads and the magnetic material combined with the acid-washed floating beads, the mercury removal efficiency of the magnetic composite material after the introduction of MXene is qualitatively improved, and the mercury removal efficiency reaches 97.91%, or even 100%.
[0055] The fly ash-based magnetic composite material of the above-mentioned embodiment 1 was tested for mercury adsorption. The method is to dilute the mercury standard solution with water to obtain a mercury-containing solution of corresponding concentration, then add a certain mass of powder sample to the solution, use an X-ray fluorescence heavy metal analyzer to test the divalent mercury concentration in the solution before and after adding the sample, and calculate the adsorption amount by the concentration difference / the mass of the powder sample used. The operating conditions are: the test mode is water, the test time is 100s, the initial divalent mercury concentration is 10, 20, 50, 100, 200, 400, 800mg / L, the solution volume is 100mL, the adsorbent dosage is 50mg, the adsorption time is 48h, and the temperature is room temperature. The experimental results are shown in Table 2.
[0056] Table 2 Adsorption amount of samples in Example 1 for different divalent mercury concentrations
[0057] Concentration of divalent mercury (mg / L) Adsorption capacity (mg / g) Equilibrium time 10 17.05 1h 20 43.05 1h 50 93.56 1h 100 225.83 1h 200 425.04 48h 400 595.17 48h 800 636.38 48h
[0058] It can be seen from Table 2 that the sample of Example 1 reached adsorption equilibrium for divalent mercury concentration solutions of 10, 20, 50, and 100 mg / L in 1 h, and the adsorption rate was very fast; as the concentration continued to increase, even at 800 mg / L, the adsorption amount reached a very considerable 636.38 mg / g, indicating that the introduction of MXene greatly improved the adsorption capacity of the sample for mercury ions.
[0059] Figure 2 The XRD patterns of the samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG.
[0060] from Figure 2 It can be seen that compared with the sample prepared in Comparative Example 1, the XRD spectra of the samples prepared in Comparative Example 2 and Example 1 show characteristic peaks of Fe3O4 at 30.1°, 35.4°, and 62.5°, indicating that Fe3O4 is successfully loaded on the fly ash, while the spectrum of Example 1 also has an additional peak of (002), indicating that MXene is successfully loaded to form MXene / Fe3O4 / FA.
[0061] Figure 3 The magnetization curves of the samples prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0062] from Figure 3 It can be seen that due to the presence of Fe3O4, the magnetic strength of the samples prepared in Comparative Example 2 and Example 1 (4.55 and 2.68 emu / g, respectively) is much higher than the fly ash (0.09 emu / g) of Comparative Example 1; the magnetic strength of the sample prepared in Example 1 is lower than that of the sample synthesized in Comparative Example 2 because MXene is wrapped on the outside, but it does not affect the magnetic properties of the sample prepared in Example 1.
[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a fly ash-based magnetic composite material, characterized in that: The following steps are involved: Add the pickled beads to the Fe-containing 3+ and Fe 2+ The solution is added, the pH is adjusted to 10, the reaction is stirred at 80°C, and the magnetic beads are obtained by filtering; the magnetic beads are dispersed in a MXene dispersion, the pH is adjusted to 5, ultrasonicated, stirred in an inert atmosphere, filtered, and dried to obtain a fly ash-based magnetic composite material; The Fe 3+ with Fe 2+ The molar ratio is 2:1; The pickling beads and the Fe 3+ The mass molar ratio of the magnetic beads and the MXene is 9:
1.
2. The method for preparing the fly ash-based magnetic composite material according to claim 1, characterized in that: The preparation steps of the acid-washed floating beads include: dispersing the floating beads into a 0.1 mol / L HCl solution, stirring for 1 hour, filtering and drying to obtain the acid-washed floating beads.
3. The method for preparing the fly ash-based magnetic composite material according to claim 1, characterized in that: The Fe-containing 3+ and Fe 2+ The solvent of the solution is ethanol and water in a volume ratio of 1:
1.
4. The method for preparing the fly ash-based magnetic composite material according to claim 1, characterized in that: The stirring reaction time at 80° C. is 3 h.
5. The method for preparing the fly ash-based magnetic composite material according to claim 1, characterized in that: The content of MXene in the MXene dispersion is 1 to 4 mg / mL.
6. The method for preparing the fly ash-based magnetic composite material according to claim 1, characterized in that: The ultrasonication time is 1 hour; the stirring time under the inert atmosphere is 1 hour.
7. A fly ash-based magnetic composite material obtained according to the method for preparing a fly ash-based magnetic composite material according to any one of claims 1 to 6.
8. Use of the fly ash-based magnetic composite material according to claim 7 in the adsorption of divalent mercury.
Citation Information
Patent Citations
Heavy metal composite curing agent as well as preparation method and application thereof
CN111974346A